2015
DOI: 10.18287/0134-2452-2015-39-5-728-737
|View full text |Cite
|
Sign up to set email alerts
|

A method for connecting antenna radiators to RoF systems using an optical device and calculating its parameters

Abstract: It is proposed that a special optical device be used to connect the radio antenna array to a Radio-over-Fiber light guide line, which provides splitting optical signals into predetermined frequency bands. The field calculation within the device active region is done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…-for the focon profile one can write: ( ) z , where n0 is initial (unperturbed by the gradient) refractive index. Thus, the undetermined function for all waves is ( , ) rz , and, as the results of similar studies presented in [32][33][34][35] show, ( , ) rz most likely will not exceed a few percents of n0. For definiteness, we set:     0 ( , ) 0,1 ( , ) r z n r z .…”
Section: Proposed Conversion Device and Formulation Of The Problem Of Modeling Its Parametersmentioning
confidence: 65%
See 2 more Smart Citations
“…-for the focon profile one can write: ( ) z , where n0 is initial (unperturbed by the gradient) refractive index. Thus, the undetermined function for all waves is ( , ) rz , and, as the results of similar studies presented in [32][33][34][35] show, ( , ) rz most likely will not exceed a few percents of n0. For definiteness, we set:     0 ( , ) 0,1 ( , ) r z n r z .…”
Section: Proposed Conversion Device and Formulation Of The Problem Of Modeling Its Parametersmentioning
confidence: 65%
“…On the contrary, significant influence have quadratic-nonlinear change in the refractive index, characterized by  (2) , when the waves propagate along the focon, and the interference of waves during transverse distribution, which ensures the addition of re-reflecting waves into a single mode. But the function F in (9) also has a z-axis dependence, moreover, as shown in [32][33][34], to obtain a proper solution one should divide the entire focon into transverse layers of width Δz where Δz →0, fig. 3.…”
Section: Modeling the Parameters Of The Proposed Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the study of even a small step in the indicated direction, demonstrating generality in obtaining the listed elements, seems to be a relevant and interesting scientific result. From this point of view, the method proposed by the authors and described in 15 can be used to create very diverse components of the form 4 .…”
Section: Proposed Approach To Obtaining Optically Transparent Complex...mentioning
confidence: 99%
“…In general, a number of works were published describing examples of fiber or fiber compatible devices, for the operation of which it is necessary to obtain a complex 3D-gradient of the refractive index profile. Thus, in 4 , a profile of a fiber-compatible guiding structure (mixer) was obtained, designed to provide a quasi-single-mode propagation of light for wavelengths of the telecommunication range (~1550 nm) with a structure diameter of 30...40 μm. Such a mixer is a key element of a fiberoptic antenna array control device, which allows direct connection of a radio segment to a RoF (Radio-over-Fiber) fiber optic line.…”
Section: Introductionmentioning
confidence: 99%